Smart Home System Using Internet Of Things (Iot) Based On Arduino Mega And Esp32 - Muttaqin Hardiwansyah; Monika Faswia Fahmi; Puteri Nurul Ma’rifah; Achmad Zain Nur; Safriudin Rifandi; Muhhammad Iyan Putra Pratama (Jurnal Teknik Elektro dan Komputer TRIAC, 2026)
Smart Home systems based on the Internet of Things (IoT) offer modern solutions to enhance efficiency, comfort, and security in managing household appliances. This research aims to develop a smart home system using Arduino Mega as the main controller and the ESP32 module as a Wi-Fi network connector. The system is designed to control devices such as lights, fans, automatic doors, and a plant watering system through an Apache-based web server connected to a MySQL database. The methods used include the design of a smart home miniature hardware prototype, the development of a web interface for manual and automatic control, as well as the integration of a voice command feature based on Google Text-to-Speech. Testing was conducted by measuring Quality of Service (QoS) parameters such as delay, throughput, packet loss, and jitter, along with functional testing of devices through manual, automatic, and voice command operations. The results show that the system can operate properly with an accuracy rate of 100%, an average delay of 4–5 seconds for device control, and an average QoS index of 1.5. Some minor delays were observed, mainly due to the use of a web server and internet connection. With affordable development costs, this system provides a practical solution for small-scale IoT-based smart home implementation.